GROWTH RATE OF Nannochloropsis sp ACCORDING TO ADDITING CONCENTRATION OF ZINC (ZN) AND COOPER (CU) - Sagala, Herlina Meria Uli; Pattirane, Chrisoetanto P; Sewiko, Roni; Wulandari, Ully; Sulistyowati, Beta Indi (Asian Journal of Aquatic Sciences, 2022)
Zinc and copper are micronutrients that are the factors that support microalgae growth rate besides macronutrients, CO2, temperature, salinity, and pH. Growth of Nannochlopsis sp was observed to determine the influence of the addition of Zn and Cu concentration. Microalgae cultivation was located outdoors on the semi-mass scale using 800 L medium on mesophilic condition in 3 treatments with the addition of 1 ppm, 3 ppm, and 5 ppm concentrations of Zn and Cu metals. Cells density was calculated using a hemocytometer, and the absorbed metal content was measured by AAS. The study aimed to test the growth response of Nannochloropsis sp cells to Zn and Cu metals. The growth rate of microalgae was observed for the addition of Zn and Cu concentration in the cultivation medium. The result showed the highest Nannochloropsis sp growth rate for Zn addition was 0.053/day and for Cu addition was 0.279/day. Between Zn and Cu addition, the highest growth rate was observed in the addition of 1 ppm Cu metal (Cu1) which was equal to 0.279/day. This shows that adding micronutrients are not automatically will increase the growth rate of microalgae as well.